Erratum: Bao, L.; Cai, W.; Zhang, X.; Liu, J.; Chen, H.; Wei, Y.; Jia, X.; Bai, Z. Distinct Microbial Community of Phyllosphere Associated with Five Tropical Plants on Yongxing Island, South China Sea. Microorganisms 2019, 7, 525 - Lijun Bao; Wenyang Cai; Xiaofen Zhang; Jinhong Liu; Hao Chen; Yuansong Wei; Xiuxiu Jia; Zhihui Bai (Microorganisms, 2020)
The authors wish to make the following erratum in this paper [...]